Penerapan Metode Saving Matrix Dalam Penjadwalan Dan Penentuan Rute Distribusi Premium Di SPBU Kota Malang - Yuniarti, Rahmi; Astuti, Murti (Rekayasa Mesin, 2013)
Several existing problems in PT. Pertamina depot Malang in distributing premium products to the gas station in Malang is the high number of premium demand is not matched by the availability of the number of vehicles as well as sufficient capacity tank trucks, and inconsistencies in the distribution schedule every day, and the lack of a clear standard distribution service. Therefore, this study would like to set up distribution routes and schedules and determine the capacity and number of tank trucks are effective and efficient in order to benefit the company. In this research, the determination of the method of saving a useful matrix to solve the problem of transportation and distribution. Based on calculations using the method of saving matrix, then the distribution of these proposals can be given as many as 16 in the three stages of the delivery so that every gas station will have no shortage of fuel supply. Successfully reduced transportation costs and shortened the distance of 261 km to 259.6 km. In the distribution of premium in Malang PT. Pertamina Depot Malang who initially use 11 tanker trucks capable streamlined into 6 tanks.Key Words : Saving Matrix, Rute and distribution schedule, transportation cost